Plot (soil) variety control as part of the varietal quality confirmation of soft wheat seed - О. В. Захарчук; С. М. Гринів; М. М. Таганцова; Н. В. Курочка (Plant Varieties Studying and Protection)
Purpose. To evaluate the effectiveness of plot (soil) variety control to confirm purity of varieties (hybrids, lines) and authenticity of seed characteristics of soft wheat varieties at all stages of seed reproduction, as well as to ensure quality assurance of the produced seed. Methods. Analysis and synthesis, comparison method, statistical analysis, systematic approach, tabular and graphical methods. Results. The study found that plot (soil) variety control is a mandatory component of the seed certification system, which ensures confirmation of varietal purity and detection of inconsistencies at the stages of production, storage and sale. Controls for pre-basic (PBS), basic (BS) and certified (CS) seed help to ensure high quality standards. In 2020–2023, the number of control samples of soft winter wheat seed passing the plot (soil) variety control decreased. This was due to military operations, logistical disruptions and a reduction in the area under cultivation. However, despite these factors, the varieties ‘Bohdana’, ‘Mudrist Odeska’ and ‘Podolianka’ remain the leaders in the number of control samples due to their stable yields and high disease resistance. Conclusions. Plot (soil) variety control plays an important role in quality assurance and detection of inconsistencies at the stages of seed production. The decrease in the number of control samples in 2020–2023 is due to military operations, reduced crop areas and economic difficulties. At the same time, the popularity of domestic wheat varieties, such as ‘Bohdana’ and ‘Mudrist Odeska’, demonstrates their high adaptability, yield and resistance to disease pathogens. To maintain and strengthen the position of the Ukrainian seed industry, it is necessary to actively develop the domestic seed market, support breeding programmes and encourage the export of domestic seed products.